Biogas-fueled flame fuel cell for micro-combined heat and power system. (15th September 2017) - Zeng, Hongyu; Wang, Yuqing; Shi, Yixiang; Cai, Ningsheng
Highlights: A micro-CHP with biogas-fueled flame fuel cell for indigenous source. Stable biogas fuel-rich combustion in porous media burner. Maximum power of 1.4 W for a single micro-tubular FFC. Analysis of performance degradation resulted from carbon deposition. Abstract: A biogas-fueled flame fuel cell (FFC) unit is proposed for the micro-combined heat and power (CHP) system using indigenous energy source. With fuel-rich flame as both heater and reformer, FFC is advantageous for quick start-up, no sealing, and simple thermal management. In this study, a porous media burner with non-catalytic fuel-rich combustion was utilized to provide both stable high temperature environment and reformed syngas for the solid oxide fuel cell (SOFC). The porous media burner and a micro-tubular SOFC were integrated directly in the biogas FFC reactor. The performance of fuel-rich combustion and electrochemical characteristic was studied for various equivalence ratios from 1.2 to 1.4. Experimental results showed that the reforming efficiency reached 42.3% with the porous media burner, using model biogas of 60% CH4 and 40% CO2 as fuel. The maximum power for a single tubular fuel cell reached 1.4 W when fed with model biogas at an equivalence ratio of 1.4. Furthermore, performance degradation caused by carbon deposition at the anode was investigated.